Perovskite solar cell and preparation method thereof
Through the introduction of perxbasus solar cells to introduce bipidimazole ring zero -dimensional perovskite, improve the crystallization and orientation of the perovskite layer, solve the problem of low long -term stability of perovskite solar cells, achieve higher efficiency and higher efficiency and stability.
Patent Information
- Application Number
- CN202411486285.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-24
AI Technical Summary
The long-term stability of existing three-dimensional perovskite solar cells is low and susceptible to ultraviolet light, oxygen, humidity, high temperature and electric fields, resulting in a shortening of the device life.
By introducing bis-imidazole ring zero-dimensional perovskite into the perovskite layer, 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium)dibromide was used. Chemicals are used to modify the perovskite layer to improve its crystallinity and orientation, reduce internal defects, and improve the mobility and lifetime of photogenerated carriers.
Improve the efficiency and stability of perovskite solar cells, enhance the moisture resistance and long -term stability of the device, and improve the performance of photovoltaic performance.
Smart Images

Figure CN119365039A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solar cells, and in particular to a perovskite solar cell and a preparation method thereof. Background Art
[0002] In the past few years, three-dimensional perovskite materials have attracted much attention due to their excellent luminescence properties and diverse components. Their advantages such as low cost, suitability for solution processing and large-area film formation make them show strong application potential in the optoelectronic field, and traditional three-dimensional perovskite solar cells have achieved remarkable photoelectric conversion efficiency of up to 25.7%. However, the long-term stability problem is a challenge that current perovskite devices urgently need to solve. Three-dimensional metal halide perovskite materials themselves are prone to ion migration, resulting in structural instability. Poor tolerance to ultraviolet light, oxygen, humidity, high temperature and electric fields sharply shortens the life of the device, becoming a key factor limiting its practical application. Therefore, under the premise of ensuring the photovoltaic performance of the device, improving the long-term stability of perovskite photovoltaic devices has become a top priority for research.
[0003] Therefore, the existing technology still needs to be improved and developed. Summary of the invention
[0004] In view of the above-mentioned deficiencies in the prior art, the present invention provides a perovskite solar cell and a preparation method thereof, aiming to solve the technical problem of low long-term stability of existing three-dimensional perovskite solar cells.
[0005] Specifically, the technical solution of the present invention is as follows:
[0006] In a first aspect, the present invention provides a method for preparing a perovskite solar cell, comprising the steps of:
[0007] providing a conductive substrate;
[0008] preparing an electron transport layer on the conductive substrate;
[0009] A perovskite layer is prepared on the surface of the electron transport layer, wherein the perovskite layer includes a perovskite body and 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide;
[0010] preparing a hole transport layer on the surface of the perovskite layer;
[0011] An electrode is prepared on the surface of the hole transport layer.
[0012] The present invention introduces a dicationic ionic liquid 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium)dibromide into a perovskite layer based on a spin coating process, and uses 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium)dibromide to modify the perovskite layer to form a novel diimidazole ring zero-dimensional perovskite, thereby improving the crystallinity and orientation of the three-dimensional perovskite layer, and improving the mobility and lifetime of photogenerated carriers, thereby improving the efficiency of the device and enhancing the moisture resistance and stability of the perovskite device.
[0013] Optionally, the step of preparing a perovskite layer on the surface of the electron transport layer specifically includes:
[0014] providing a mixed solution of lead iodide and 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide, and providing an organic halide solution;
[0015] Spin coating a mixed solution of the lead iodide and 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide on the surface of the electron transport layer, and performing a first annealing treatment to obtain a lead iodide layer;
[0016] The organic halide solution is spin-coated on the surface of the lead iodide layer, and subjected to a second annealing treatment to obtain the perovskite layer.
[0017] The present invention introduces 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide into a lead iodide solution, and adopts a two-step spin coating technology to prepare the perovskite layer. The two-step spin coating method is used to prepare the perovskite layer, and the preparation process is simple, the repetition rate is high, anti-solvents such as chlorobenzene are removed, the cost is effectively reduced, and the device is more environmentally friendly, and rapid large-area device preparation and production can be achieved.
[0018] Optionally, the molar ratio of the 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide to the lead iodide is 0.0005-0.005:1.
[0019] Optionally, the method for preparing the mixed solution of lead iodide and 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide comprises the steps of:
[0020] dissolving lead iodide in a solvent to obtain a lead iodide solution;
[0021] Adding 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide to the lead iodide solution to obtain a mixed solution of the lead iodide and 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide;
[0022] Optionally, the solvent is selected from one or more of N,N-dimethylformamide, dimethyl sulfoxide, and N-methylpyrrolidone.
[0023] Optionally, in the step of spin coating the mixed solution of lead iodide and 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide on the surface of the electron transport layer, the spin coating parameters include: a rotation speed of 1000-5000 r / s and a time of 20-60 s;
[0024] And / or, the parameters of the first annealing treatment include: temperature of 50-100° C. and time of 20-100 s.
[0025] Optionally, the organic halide solution is a solution containing FAI, MACl, and MABr.
[0026] Optionally, the mass ratio of FAI, MACl and MABr is 60:(5-10):(5-9).
[0027] Optionally, in the step of spin coating the organic halide solution on the surface of the lead iodide layer, the spin coating parameters include: a rotation speed of 1000-5000 r / s and a time of 20-60 s;
[0028] And / or, the parameters of the second annealing treatment include: temperature of 90-150° C. and time of 40-80 min.
[0029] In a second aspect, the present invention provides a perovskite solar cell prepared by the perovskite solar cell preparation method.
[0030] The present invention has the following beneficial effects:
[0031] The present invention provides a perovskite solar cell and a preparation method thereof, wherein a bisimidazole ring molecule 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide is used to modify a perovskite layer to form a novel bisimidazole ring zero-dimensional perovskite, and the crystallinity and orientation of the three-dimensional perovskite layer are improved, while the defects inside the perovskite are reduced, and the mobility and life of the photogenerated carriers are improved, thereby improving the efficiency of the device and enhancing the moisture resistance and stability of the perovskite device. Moreover, 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide has a strong interaction with lead iodide, which enhances the anchoring effect on lead ions, thereby improving the photovoltaic performance and stability of the device. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 Schematic diagram of the single crystal structure of a zero-dimensional perovskite containing 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide in an embodiment of the present invention.
[0033] Figure 2 This is a single crystal optical picture of a zero-dimensional perovskite containing 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide in an embodiment of the present invention.
[0034] Figure 3 Scanning electron microscope images of the zero-dimensional perovskite / three-dimensional perovskite film containing 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide and the three-dimensional perovskite film of the control group in the embodiment of the present invention.
[0035] Figure 4 Graph showing the photoelectric conversion efficiency of zero-dimensional perovskite / three-dimensional perovskite containing 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide and a control group three-dimensional perovskite thin film device in an embodiment of the present invention. DETAILED DESCRIPTION
[0036] The present invention provides a perovskite solar cell and a method for preparing the same. To make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the scope of protection of the present invention.
[0037] Under the premise of ensuring the photovoltaic performance of the device, the present invention proposes an innovative component regulation strategy, introducing 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide to modify the three-dimensional perovskite. It is an effective method to construct a zero-dimensional / three-dimensional material that conforms to the perovskite structure. It can make full use of the excellent stability of the zero-dimensional perovskite material. At the same time, the three-dimensional structure provides a strong guarantee for the efficiency of the device, thereby preparing an efficient and stable perovskite solar cell.
[0038] An embodiment of the present invention provides a method for preparing a perovskite solar cell, which comprises the steps of:
[0039] (1) providing a conductive substrate;
[0040] (2) preparing an electron transport layer on the conductive substrate;
[0041] (3) preparing a perovskite layer on the surface of the electron transport layer, wherein the perovskite layer comprises a perovskite body and 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide;
[0042] (4) preparing a hole transport layer on the surface of the perovskite layer;
[0043] (5) Preparing an electrode on the surface of the hole transport layer.
[0044] In the embodiment of the present invention, a bisimidazole ring molecule 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium)di(bromide) is introduced into the perovskite layer, and its chemical formula is: The molecule has two imidazole rings, each of which is connected to a butyl group, and the imidazole rings are connected by a carbon chain. The perovskite layer is modified using 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide to form a new type of double imidazole ring zero-dimensional perovskite, which is distributed in the three-dimensional perovskite and can improve the crystallinity and orientation of the three-dimensional perovskite layer, passivate the defects inside the three-dimensional perovskite, and improve the mobility and lifetime of photogenerated carriers, thereby improving the efficiency of the device. It can also improve the stability of the perovskite film and enhance the moisture resistance and stability of the perovskite device. In addition, 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide can produce a strong interaction with lead iodide, enhance the anchoring effect on lead ions, and thus improve the photovoltaic performance and stability of the device.
[0045] In step (1), the conductive substrate is a rigid conductive substrate or a flexible conductive film substrate. Further, the rigid conductive substrate may be, but is not limited to, an ITO conductive glass substrate, an FTO conductive glass substrate, etc. Further, the flexible conductive film substrate may be, but is not limited to, a PET film substrate, a PEN film substrate, etc.
[0046] The conductive substrate is a conductive substrate that has been cleaned and UV treated. Specifically, the conductive substrate is first cleaned, and the conductive substrate is ultrasonically cleaned with a detergent aqueous solution, deionized water, ethanol and isopropanol in sequence, and then blown dry with nitrogen. Then, the cleaned conductive substrate is treated with ultraviolet ozone to improve the hydrophilicity of the conductive substrate.
[0047] In step (2), the step of preparing an electron transport layer on the conductive substrate specifically includes:
[0048] preparing an electron transport material solution;
[0049] The electron transport material solution is coated on the treated conductive substrate and annealed to obtain the electron transport layer.
[0050] The electron transport material may be an organic electron transport material, such as fullerene derivatives PCBM or C60, etc. The electron transport material may also be an inorganic electron transport material solution, such as titanium dioxide solution or tin dioxide solution, etc.
[0051] In step (3), in some embodiments, the step of preparing a perovskite layer on the surface of the electron transport layer specifically includes:
[0052] providing a mixed solution of lead iodide and 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide, and providing an organic halide solution;
[0053] Spin coating a mixed solution of the lead iodide and 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide on the surface of the electron transport layer, and performing a first annealing treatment to obtain a lead iodide layer;
[0054] The organic halide solution is spin-coated on the surface of the lead iodide layer, and subjected to a second annealing treatment to obtain the perovskite layer.
[0055] In a specific embodiment, the perovskite layer solution is prepared in two parts, namely, a mixed solution of lead iodide and 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide and an organic halide solution. After accurately weighing the drugs, solvents are added respectively and dissolved evenly to obtain a mixed solution of lead iodide and 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide and an organic halide solution. The perovskite layer is obtained after two-step spin coating and two-step annealing operations.
[0056] In this embodiment, a two-step spin coating process is used. In the first step, a bisimidazole ring molecule, namely 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide, is introduced into the lead iodide solution to modify it. There is a van der Waals force between the imidazole ring and the lead iodide, which can effectively delay the reaction of lead iodide and the organic salt, resulting in a slower crystallization rate of the perovskite, which is conducive to the formation of a high-quality perovskite film with higher crystallinity. At the same time, the bisimidazole ring molecule 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide can react with lead iodide to form a zero-dimensional perovskite, which is distributed in the three-dimensional perovskite and passivates the defects of the three-dimensional perovskite. Generally, the traditional method of placing an ionic liquid layer between the electron transport layer and the perovskite light-absorbing layer can passivate the defects of the perovskite interface and has little effect on the crystallinity of the perovskite itself. In comparison, the present invention introduces 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide into the lead iodide solution, which not only forms zero-dimensional perovskite passivation defects, but also can significantly improve the crystallinity and orientation of the perovskite, improve the mobility and life of photogenerated carriers, thereby improving the efficiency of the device and enhancing the moisture resistance and stability of the perovskite device. In addition, 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide has a strong interaction with lead iodide, which enhances the anchoring effect on lead ions, thereby improving the photovoltaic performance and stability of the device.
[0057] After the organic halide solution is added in the second step, a perovskite layer with larger grains and smaller defects is formed, thereby promoting the carrier mobility and crystallinity of the perovskite layer, and enhancing the stability and water resistance of the perovskite device, thereby improving the photoelectric conversion efficiency of the device. In addition, the two-step spin coating method is used to prepare the perovskite layer. The preparation process is simple, the technology is mature, the repetition rate is high, and anti-solvents such as chlorobenzene are removed, which effectively reduces costs and is more environmentally friendly, and can achieve rapid large-area device preparation and production.
[0058] In some embodiments, the molar ratio of the 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide to the lead iodide is 0.0005-0.005: 1. Specifically, when the amount of lead iodide added to the mixed solution is 1.5 mol, the amount of 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide added may be 0.1-1.0 mg, and in a preferred embodiment, the amount of 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide added may be 0.5 mg. When too little 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide is added, the effect of passivating defects and affecting the crystallization of perovskite is not obvious; when too much 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide is added, a large amount of zero-dimensional perovskite is formed, which may destroy the bulk structure of the three-dimensional perovskite and lead to a decrease in performance.
[0059] In some embodiments, the method for preparing the mixed solution of lead iodide and 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide comprises the steps of:
[0060] dissolving lead iodide in a solvent to obtain a lead iodide solution;
[0061] Adding 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide to the lead iodide solution to obtain a mixed solution of the lead iodide and 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide;
[0062] In some embodiments, the solvent is selected from one or more of N,N-dimethylformamide (DMF), dimethyl sulfoxide (DMSO), and N-methylpyrrolidone (NMP).
[0063] In some embodiments, in the step of spin coating the mixed solution of lead iodide and 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide on the surface of the electron transport layer, the spin coating parameters include: a rotation speed of 1000-5000 r / s and a time of 20-60 s; preferably, a rotation speed of 1500 r / s and a time of 30 s.
[0064] In some embodiments, the parameters of the first annealing treatment include: a temperature of 50-100° C. and a time of 20-100 s. Preferably, the temperature is 70° C. and the time is 60 s.
[0065] In this step, lead iodide reacts with 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide, which can effectively slow down the reaction of the organic salt and lead iodide in the second step, thereby slowing down the crystallization process of the perovskite, which is conducive to the formation of high-quality films.
[0066] In some embodiments, the organic halide solution is a solution containing FAI, MACl, and MABr. The solvent may be, but is not limited to, IPA, etc. The use of mixed cations and halogens is more conducive to the transformation of the perovskite phase and inhibits the formation of the non-perovskite phase.
[0067] In some embodiments, the mass ratio of FAI, MACl, and MABr is 60:(5-10):(5-9). Using mixed cations and halogens within this mass ratio range is more conducive to the transformation of the perovskite phase and inhibits the formation of the non-perovskite phase.
[0068] In some embodiments, in the step of spin coating the organic halide solution on the surface of the lead iodide layer, the spin coating parameters include: a rotation speed of 1000-5000 r / s and a time of 20-60 s. Preferably, the rotation speed is 1500 r / s and the time is 30 s.
[0069] In some embodiments, the parameters of the second annealing treatment include: a temperature of 90-150° C. and a time of 40-80 min. Preferably, the temperature is 135° C. and the time is 60 min.
[0070] In step (4), the step of preparing a hole transport layer on the surface of the perovskite layer specifically includes:
[0071] providing a hole transport material solution;
[0072] The hole transport material solution is coated on the surface of the perovskite layer and annealed to form the hole transport layer.
[0073] The hole transport material solution may be an organic hole transport material, such as Spiro-OMeTAD (2,2',7,7'-tetrakis(N,N-p-methoxyanilino)-9,9'-spirobifluorene), PEDOT:PSS (poly-3,4-ethylenedioxythiophene:polystyrenesulfonic acid), etc. The hole transport material solution may also be an inorganic hole transport material, such as nickel oxide or cuprous thiocyanate, etc.
[0074] In step (5), a metal electrode can be prepared on the surface of the hole transport layer by evaporation, and finally a perovskite solar cell is obtained.
[0075] The embodiment of the present invention further provides a perovskite solar cell, which is prepared by using the preparation method of the perovskite solar cell.
[0076] The scheme of the present invention is further described below with specific embodiments.
[0077] Comparative Example 1
[0078] (1) Cleaning of rigid conductive ITO substrate: Soak in detergent aqueous solution, deionized water and isopropyl alcohol for ultrasonic cleaning for 15 minutes respectively, and then blow dry with nitrogen.
[0079] (2) Prepare the tin dioxide electron transport layer by spin coating. Place the treated ITO transparent substrate in a UV instrument and treat with ozone for 30 minutes. Prepare a tin dioxide solution (the volume ratio of tin dioxide solution to deionized water solution is 1:5). The spin coating speed is 4000 r / s and the acceleration is 4000 r / s. 2 , run for 30 seconds. Drop the tin dioxide solution on the UV treated ITO surface and start spin coating. After the end, place the sample on a heating table and anneal at 150°C for 30 minutes. After annealing, set aside.
[0080] (3) Prepare a solution for the perovskite active layer. Dissolve 1.5 mol of lead iodide in 1 mL of DMF solution to prepare a mixed solution of lead iodide and 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide. The mass concentration of the FAI:MACl:MABr solution is 60:6:6 mg / mL IPA solution, stir evenly and set aside.
[0081] (4) The preparation of the perovskite active layer is divided into two steps. The first step: UV treatment of the ITO substrate with an electron transport layer on the surface for 30 minutes. Set the parameters of the spin coater: the rotation speed is 1500r / s, the acceleration is 1500r / s 2 , run for 30 seconds. Drop the mixed solution of lead iodide and 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide on the substrate surface and turn on the spin coater. After the spin coating is completed, anneal at 70℃ for 60 seconds and then cool for use. Step 2: Add FAI:MACl:MABr mixed solution based on the first step, and the spin coater parameters are the same as the first step. After the spin coating is completed, place the sample on a heating table, anneal at 100℃ for 50 minutes, and then cool for use.
[0082] (5) Prepare the spiro-OMeTAD hole transport layer by spin coating. In this embodiment, spiro-OMeTAD solution was spin coated. The spiro-OMeTAD solution was prepared as follows: 72.5 mg spiro-OMeTAD, 36 ul TBP solution, 30 ul LiTFSI solution (260 mg LiTFSI / 1 ml acetonitrile) were mixed in 1 ml chlorobenzene. The parameters of the spin coater were set as follows: the rotation speed was 4000 r / s, the acceleration was 4000 r / s2 After spin coating, the device was placed in a dark place for 12 hours, and then a gold electrode with a thickness of about 80 nm was evaporated to complete the device preparation.
[0083] Example 1
[0084] (1) Cleaning of rigid conductive ITO substrate: Soak in detergent aqueous solution, deionized water and isopropyl alcohol for ultrasonic cleaning for 15 minutes respectively, and then blow dry with nitrogen.
[0085] (2) Prepare the tin dioxide electron transport layer by spin coating. Place the treated ITO transparent substrate in a UV instrument and treat with ozone for 30 minutes. Prepare a tin dioxide solution (the volume ratio of tin dioxide solution to deionized water solution is 1:5). The spin coating speed is 4000 r / s and the acceleration is 4000 r / s. 2 , run for 30 seconds. Drop the tin dioxide solution on the UV treated ITO surface and start spin coating. After the end, place the sample on a heating table and anneal at 150°C for 30 minutes. After annealing, set aside.
[0086] (3) Prepare a solution for the perovskite active layer. Dissolve 1.5 mol of lead iodide in 1 mL of DMF solution, then add 0.5 mg of 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide to prepare a mixed solution of lead iodide and 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide. The mass concentration of FAI:MACl:MABr solution is 60:6:6 mg / mL IPA solution, stir evenly and set aside.
[0087] (4) The preparation of the perovskite active layer is divided into two steps. The first step: UV treatment of the ITO substrate with an electron transport layer on the surface for 30 minutes. Set the parameters of the spin coater: the rotation speed is 1500r / s, the acceleration is 1500r / s 2 , run for 30 seconds. Drop a mixed solution of lead iodide and 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide on the substrate surface and turn on the spin coater. After spin coating, anneal at 70°C for 60 seconds and cool for use. Step 2: Add FAI:MACl:MABr mixed solution based on the first step, and the spin coater parameters are the same as the first step. After spin coating, place the sample on a heating table, anneal at 100°C for 50 minutes, and cool for use.
[0088] (5) Prepare the spiro-OMeTAD hole transport layer by spin coating. In this embodiment, spiro-OMeTAD solution was spin coated. The spiro-OMeTAD solution was prepared as follows: 72.5 mg spiro-OMeTAD, 36 ul TBP solution, 30 ul LiTFSI solution (260 mg LiTFSI / 1 ml acetonitrile) were mixed in 1 ml chlorobenzene. The parameters of the spin coater were set as follows: the rotation speed was 4000 r / s, the acceleration was 4000 r / s 2 After spin coating, the device was placed in a dark place for 12 hours, and then a gold electrode with a thickness of about 80 nm was evaporated to complete the device preparation.
[0089] Example 2
[0090] (1) Cleaning of rigid conductive substrate FTO material. First, put the FTO substrate material into a beaker, first ultrasonically clean it in deionized water and detergent solution for 30 minutes, then ultrasonically clean it in deionized water for 30 minutes, and finally ultrasonically clean it in isopropanol solution for 30 minutes. After completion, blow dry it with nitrogen.
[0091] (2) Prepare the tin dioxide electron transport layer by spin coating. Place the treated FTO transparent substrate in a UV instrument and treat with ozone for 30 minutes. Prepare a tin dioxide solution (the volume ratio of tin dioxide solution to deionized water solution is 1:6). Set the parameters of the spin coater: the rotation speed is 3000 r / s, the acceleration is 3000 r / s 2 , run for 30 seconds. Drop the tin dioxide solution on the UV-treated FTO surface, turn on the spin coater, and after the spin coating is completed, place the sample on a heating table and anneal at 180°C for 60 minutes. After the annealing is completed, set aside.
[0092] (3) Prepare the solution of the perovskite active layer. 1.5 mol of lead iodide was dissolved in a mixed solution of 950 μL DMF and 50 μL DMSO, and then 0.3 mg of 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide powder was added to prepare a mixed solution of lead iodide and 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide. The mass concentration of FAI:MACl:MABr solution was 60:10:8 mg / mL IPA solution, which was stirred evenly for use.
[0093] (4) The preparation of the perovskite active layer is divided into two steps. The first step: UV treatment of the FTO substrate with an electron transport layer on the surface for 30 minutes. Set the parameters of the spin coater: the rotation speed is 2000r / s, the acceleration is 2000r / s 2, run for 40 seconds. Drop a mixed solution of lead iodide and 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide on the substrate surface and turn on the spin coater. After spin coating, anneal at 75°C for 50 seconds and cool for use. Step 2: Add a mixed solution containing FAI:MACl:MABr on the basis of the first step, and the spin coating strip is the same as the first step. After spin coating, place the sample on a heating table, anneal at 150°C for 40 minutes, and cool for use.
[0094] (5) Prepare the spiro-OMeTAD hole transport layer by spin coating. In this embodiment, spiro-OMeTAD solution was spin coated. The spiro-OMeTAD solution was prepared as follows: 72.5 mg spiro-OMeTAD, 36 ul TBP solution, 30 ul LiTFSI solution (260 mg LiTFSI / 1 ml acetonitrile) were mixed in 1 ml chlorobenzene. The parameters of the spin coater were set as follows: the rotation speed was 4000 r / s, the acceleration was 4000 r / s 2 , run for 30 seconds. After spin coating, it was left to oxidize overnight, and then a gold electrode with a thickness of about 80nm was evaporated to complete the preparation of the perovskite solar cell.
[0095] Example 3
[0096] (1) Cleaning of rigid conductive substrate ITO material: Soak in detergent aqueous solution, deionized water and isopropyl alcohol for ultrasonic cleaning for 15 minutes respectively, and then blow dry with nitrogen.
[0097] (2) Prepare the PEDOT:PSS hole transport layer by spin coating. Mix the purchased PEDOT:PSS and ethanol in a ratio of 1:3 and filter with a filter head with a pore size of 45 nm. Spin coat the filtered solution on the ITO surface treated in (1) at a spin coating speed of 4000 r / s and an acceleration of 2000 r / s. 2 , run for 60 seconds. After spin coating, anneal at 150℃ for half an hour and cool for later use.
[0098] (3) Prepare the solution of the perovskite active layer. 1.5 mol of lead iodide was dissolved in a mixed solution of 900 μL DMF and 100 μL DMSO, and then 1.0 mg of 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide powder was added to prepare a mixed solution of lead iodide and 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide. The mass concentration of the FAI:MACl:MABr solution was 90:6:9 mg / mL IPA solution, which was mixed and set aside.
[0099] (4) The preparation of the perovskite active layer is divided into two steps. The first step: UV treatment of the ITO substrate with an electron transport layer on the surface for 30 minutes. Set the parameters of the spin coater: the rotation speed is 2000r / s, the acceleration is 2000r / s 2 , run for 30 seconds. Drop a mixed solution of lead iodide and 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide on the substrate surface and turn on the spin coater. After spin coating, anneal at 70°C for 75 seconds and cool for use. Step 2: Add FAI:MACl:MABr mixed solution based on the first step, and the spin coater parameters are the same as the first step. After spin coating, place the sample on a heating table, anneal at 125°C for 30 minutes, and cool for use.
[0100] (5) Finally, C60 (28 nm), BCP (8 nm) and Ag (90 nm) were evaporated using a vacuum thermal evaporator to complete the preparation of the perovskite solar cell.
[0101] Example 4
[0102] (1) Cleaning of the conductive substrate ITO material: Soak in a detergent aqueous solution, deionized water and isopropyl alcohol for ultrasonic cleaning for 15 minutes, and then blow dry with nitrogen.
[0103] (2) The nickel oxide electron transport layer was prepared by spin coating. 0.1 mol L -1 Nickel acetate was dissolved in 5 ml of ethanol, and then 0.05 ml of ethanolamine was slowly added dropwise, followed by stirring for 4 hours. The obtained solution was spin-coated on the ITO surface treated in (1), with a rotation speed of 3000 r / s and an acceleration of 1500 r / s. 2 , run for 30 seconds. After spin coating, anneal at 280℃ for one hour, cool to room temperature and set aside.
[0104] (3) Prepare a solution for the perovskite active layer. Dissolve 1.5 mol of lead iodide in 1 mL of NMP solution, then add 0.5 mg of 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide powder to prepare a mixed solution of lead iodide and 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide. The mass concentration of the FAI:MACl:MABr solution is 60:5:5 mg / mL of IPA solution, stir evenly and set aside.
[0105] (4) The preparation of the perovskite active layer is divided into two steps. Step 1: UV-treat the substrate prepared in step (2) for 20 minutes. Set the spin coating speed to 1500 r / s and the acceleration to 1500 r / s. 2, run for 30s. Drop a mixed solution of lead iodide and 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide on the substrate surface and start spin coating. After completion, anneal at 70℃ for 60 seconds and cool for use. Step 2: Add FAI:MACl:MABr mixed solution based on the first step, and the conditions are the same as the first step. After completion, place the sample on a heating table, anneal at 135℃ for 30 minutes, and cool for use.
[0106] (5) A PCBM hole transport layer was prepared by spin coating. In this embodiment, PCBM solution was spin coated. The preparation of PCBM solution was as follows: 30 mg PCBM was dissolved in 1 ml chlorobenzene. The rotation speed was 3000 r / s and the acceleration was 3000 r / s. 2 , run for 40 seconds. After spin coating, the silver electrode with a thickness of about 90nm is evaporated to complete the preparation of the perovskite solar cell.
[0107] The photoelectric conversion efficiency of the perovskite solar cells prepared in Examples 1-4 and Comparative Example 1 was tested using a solar simulator after steady-state calibration. The test results are shown in Table 1.
[0108] Table 1
[0109]
[0110]
[0111] As can be seen from Table 1, the zero-dimensional perovskite modification of the biimidazole ring in the perovskite film effectively improves its photoelectric conversion efficiency.
[0112] like Figure 1 As shown, it can be seen that the crystal structure of the perovskite formed by the introduction of 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide into the perovskite layer is a zero-dimensional perovskite.
[0113] like Figure 2 As shown, the shape of the zero-dimensional perovskite single crystal formed by 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide is bulk.
[0114] like Figure 3 As shown, by comparing the scanning electron microscope images of the zero-dimensional perovskite / three-dimensional perovskite containing 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide and the three-dimensional perovskite film prepared in Comparative Example 1, it can be seen that after the modification of the biimidazole ring molecule, the grain size of the three-dimensional perovskite is significantly increased, the surface is more uniform and smooth, and obvious zero-dimensional perovskite can be seen on the surface.
[0115] like Figure 4As shown, by comparing the photoelectric conversion efficiency diagram of the zero-dimensional perovskite / three-dimensional perovskite modified with 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide and the three-dimensional perovskite thin film device in Comparative Example 1, it can be seen that the zero-dimensional perovskite / three-dimensional perovskite modified with 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide significantly passivates defects, enhances charge transfer and extraction, and the photoelectric conversion efficiency of the device is significantly improved.
[0116] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.
Claims
1. A method for preparing a perovskite solar cell, characterized in that: Includes steps: providing a conductive substrate; preparing an electron transport layer on the conductive substrate; A perovskite layer is prepared on the surface of the electron transport layer, wherein the perovskite layer includes a perovskite body and 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide; preparing a hole transport layer on the surface of the perovskite layer; An electrode is prepared on the surface of the hole transport layer.
2. The method for preparing a perovskite solar cell according to claim 1, characterized in that: The step of preparing a perovskite layer on the surface of the electron transport layer specifically comprises: providing a mixed solution of lead iodide and 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide, and providing an organic halide solution; Spin coating a mixed solution of the lead iodide and 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide on the surface of the electron transport layer, and performing a first annealing treatment to obtain a lead iodide layer; The organic halide solution is spin-coated on the surface of the lead iodide layer, and subjected to a second annealing treatment to obtain the perovskite layer.
3. The method for preparing a perovskite solar cell according to claim 2, characterized in that: The molar ratio of the 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide to the lead iodide is 0.0005-0.005:
1.
4. The method for preparing a perovskite solar cell according to claim 2, characterized in that: The method for preparing a mixed solution of lead iodide and 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide comprises the steps of: dissolving lead iodide in a solvent to obtain a lead iodide solution; 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide is added to the lead iodide solution to obtain a mixed solution of the lead iodide and 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide.
5. The method for preparing a perovskite solar cell according to claim 4, characterized in that: The solvent is selected from one or more of N,N-dimethylformamide, dimethyl sulfoxide, and N-methylpyrrolidone.
6. The method for preparing a perovskite solar cell according to claim 2, characterized in that: In the step of spin coating the mixed solution of lead iodide and 1,1'-(ethane-1,2-diyl)bis(3-butyl-1H-imidazol-3-ium) dibromide on the surface of the electron transport layer, the spin coating parameters include: a rotation speed of 1000-5000 r / s and a time of 20-60 s; And / or, the parameters of the first annealing treatment include: temperature of 50-100° C. and time of 20-100 s.
7. The method for preparing a perovskite solar cell according to claim 2, characterized in that: The organic halide solution is a solution containing FAI, MACl and MABr.
8. The method for preparing a perovskite solar cell according to claim 7, characterized in that: The mass ratio of the FAI, MACl and MABr is 60:(5-10):(5-9).
9. The method for preparing a perovskite solar cell according to claim 2, characterized in that: In the step of spin coating the organic halide solution on the surface of the lead iodide layer, the spin coating parameters include: a rotation speed of 1000-5000 r / s and a time of 20-60 s; And / or, the parameters of the second annealing treatment include: temperature of 90-150° C. and time of 40-80 min.
10. A perovskite solar cell, characterized in that: The perovskite solar cell is prepared by the preparation method of any one of claims 1 to 9.